2009
DOI: 10.1074/jbc.m109.036186
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cδ Supports Survival of MDA-MB-231 Breast Cancer Cells by Suppressing the ERK1/2 Pathway

Abstract: Mechanisms that mediate apoptosis resistance are attractive therapeutic targets for cancer. Protein kinase C␦ (PKC␦) is considered a pro-apoptotic factor in many cell types. In breast cancer, however, it has shown both pro-survival and pro-apoptotic effects. Here, we report for the first time that down-regulation of PKC␦ per se leads to apoptosis of MDA-MB-231 cells. Inhibition of MEK1/2 by either PD98059 or U0126 suppressed the induction of apoptosis of PKC␦-depleted MDA-MB-231 cells but did not support survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 44 publications
0
47
1
Order By: Relevance
“…If the observation that younger chondroblasts have the highest ERK activity in HDC is taken into consideration, it seems to be plausible to conclude that the persistently elevated ERK1/2 activity may block further differentiation of chondroblasts and in this way could be a factor involved in the complete inhibition of in vitro cartilage matrix production following PKCdelta gene silencing. However, application of gene silencing of PKCdelta had variable effects on MEK-ERK1/2 signalling pathway in different systems [39,41,42], but the majority of the investigations describes PKCdelta as a negative regulator of MEK-ERK1/2 pathway [43]. As we failed to detect any elevation in the phosphorylation of ERK1/2, instead, we found a decreasing pattern following the application of rottlerin, therefore we suppose that this compound is probably not a PKCdelta inhibitor in HDC.…”
Section: Discussioncontrasting
confidence: 52%
“…If the observation that younger chondroblasts have the highest ERK activity in HDC is taken into consideration, it seems to be plausible to conclude that the persistently elevated ERK1/2 activity may block further differentiation of chondroblasts and in this way could be a factor involved in the complete inhibition of in vitro cartilage matrix production following PKCdelta gene silencing. However, application of gene silencing of PKCdelta had variable effects on MEK-ERK1/2 signalling pathway in different systems [39,41,42], but the majority of the investigations describes PKCdelta as a negative regulator of MEK-ERK1/2 pathway [43]. As we failed to detect any elevation in the phosphorylation of ERK1/2, instead, we found a decreasing pattern following the application of rottlerin, therefore we suppose that this compound is probably not a PKCdelta inhibitor in HDC.…”
Section: Discussioncontrasting
confidence: 52%
“…PKC-δ-induced cell proliferation in murine mammary cells is associated with activation of ERK/MAPK [22]. In contrast, PKC-δ-induced suppression of ERK1/2 is associated with the survival of MDA-MB-231 cells [33]. PKC-δ attenuates apoptosis by inducing phosphorylation and proteasomal degradation of the proapoptotic protein Bim via the MEK/MAPK pathway in immortalized and malignant keratinocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…High PKCα levels were also associated with poorer survival of the patients [7]. PKCδ and PKCε are survival factors, particularly in estrogen receptor-negative breast cancer cells [8]. Furthermore, both PKCδ and PKCε contribute to resistance to a wide range of death stimuli [9,10], and PKCε expression levels in tumors have been suggested to be associated with worse outcome for breast cancer patients [11].…”
Section: Introductionmentioning
confidence: 97%
“…We have recently demonstrated that the estrogen receptor-negative MDA-MB-231 breast cancer cell line depends on PKCα for optimal growth under serum-free conditions [7] and on PKCδ for survival [8]. To gain more insight into mechanisms behind these isoform-specific functions, we down-regulated PKCα, PKCδ and PKCε specifically in this cell line and analyzed consequences on global mRNA expression.…”
Section: Introductionmentioning
confidence: 99%